Burgerdijk’s Institutionem Logicarum and the Freedom to Print Books of the Dutch School Order - Stef van Gompel (Early Modern Low Countries)
After the States of Holland passed the School Order of 1625, which listed the schoolbooks which were to be used in the Latin schools, they refused to grant privileges protecting the books that were being prepared for this purpose. In 1626, however, the States-General granted a privilege to one of the books of the School Order, Burgersdijk’s Institutionum Logicarum. While it is often reported that this privilege was subsequently invalidated by the States of Holland, because it did not match their policy that anyone was allowed to print and publish copies of official textbooks, this article establishes that Burgersdijk’s privilege actually endured until the mid-seventeenth century. It was prolonged on two occasions by the States-General, the second time even with endorsement by the States of Holland through an attache. This means that the persistent myth about the supposed absence of privileges for Dutch schoolbooks is not entirely correct. There was obviously a need to protect some textbooks, a need the Dutch authorities also recognised. This included schoolbooks to which new elements (such as notes or indexes) were added and schoolbooks for which there was also a market outside the Latin schools, as was clearly the case for Burgersdijk’s Institutionum Logicarum.